56. A NEW AGE IN PGT-M: A DECADE´S EXPERIENCE AND NEW CHALLENGES TO DEAL WITH. (August 2019) - Bustamante-Aragones, A.; Gallego-Merlo, J.; Lorda-Sanchez, I.; Rodriguez De Alba, M.; Avila-Fernandez, A.; Arteche-Lopez, A.; Velez-Monsalve, C.; Hernandez-Rodriguez, C.; Rodriguez, L.; Linares, C.; Gago, M.; Galan, I.; et al.
Abstract : Introduction: Genetic diagnosis has evolved dramatically mainly due to application of NGS approaches. Identification of mutations in different genes related with the disease and interpretation of pathogenicity of the new genetic variants found are some of the new challenges to face with. Preimplantation Genetic Testing for Monogenic Disorders (PGT-M) is applied for disease-causing genetic variants (Likely Pathogenic and Pathogenic). In parallel, Assisted Reproduction Techniques (ART) without PGT is not allowed in Spain if there is a high risk of transmitting a severe genetic disease. Therefore, clinical classification of genetic variant as pathogenic/bening is crucial for patients and it directly impacts in their future reproductive options. Spanish National legislation about ART/PGT-M approaches and best practice guidelines are currently not enough to solve some of these PGT-M requests. The aim of this work is to report our general experience since 2008 as a reference center for PGT-M in a Public Health System and the evolution of the complexity in the evaluation of the cases. Material&Methods: From 2008-2017 a total of 372 cycles for PGT-M (202 families and 59 different monogenic diseases) including 5 PGT-HLA cases have been studied. Embryo biopsy was performed in 268 cases: 156 cases from 2007-2015 and 112 cases from 2016-2017. The genetic analysis was performed by cleavage aspiration and blastomere analysis was carried out by STR haplotype and Sanger sequencing. Clinical meeting minutes available from 2017 have been revised to analyze cases that were individually evaluated by a panel of specialists due to a Variant of Uncertain Significance (VUS) or diseases with an incomplete penetrance. Results: During this decade the number of PGT-M requests has increased an average of 25% per year. Embryo genetic analysis was performed in 72% of the cycles with a 95% transfer rate. The Clinical Pregnancy rate (%per OR, % per Transfer) has been 23% and 29%, respectively. First cases requiring compound PGT-M of two different genetic alterations were requested between 2016-2017: 3 cases involved two different monogenic diseases and 1 case involved a monogenic disease and a chromosomal rearrangement (3, 57% of the total PGT-M cases in this period). In 2017, four PGT-M cases with a VUS in COL1A2, MYH7, PKD1 and BRCA2 genes and two cases with an incomplete penetrance disease (Parkinson and FMF) needed previous evaluation by the specialist's panel. Based on the familial history, the VUS were reclassified as Probably Pathogenic in the four cases. The two cases with an incomplete penetrance were sent to the National Human Reproduction National Committee (CNRH) with a favorable resolution for the Parkinson´s case. Conclusions: The PGT-M scenario is getting more complex especially due to that NGS-based analysis is becoming more informative and extensive. This complexity implies that additionally to the progress in technical approaches for PGT-M, the previous genetic/clinical evaluation of PGT families is of great importance. In this new age of PGT-M a multidisciplinary team of geneticists, gynecologists and occasionally other specialists, is becoming essential for an appropriate evaluation of PGT-M cases.